Analisis Kemampuan Pemahaman Konsep Fisika Peserta Didik SMA Di Bantul Pada Materi Fluida Statis Dan Upaya Peningkatannya Melalui Model Pembelajaran Visualization Auditory Kinesthetic - Putri Rose Amanda Puri; Riki Perdana (MAGNETON: Jurnal Inovasi Pembelajaran Fisika UNWIRA, 2023)
As a science that studies natural phenomena, physics learning requires students' concept understanding ability. However, in reality the ability to understand the concept of students is still low. This study aims to determine the level of understanding of physics concepts of students on static fluid material. Descriptive method with survey studies research form was used in this research. This study involved 31 students of class XI SMA N 1 Kretek as the research sample. The results showed that the understanding of physics concepts of students in class XI SMA N 1 Kretek in the 2022/2023 school year on static fluid material was in the poor category with an average value of 47.7. The development of learning media such as interactive multimedia based on the Visualization, Auditory, Kinesthetic (VAK) learning model equipped with experimental learning methods can be an alternative to improve the ability to understand the physics concepts of students.